Comparison Between Isoflurane and Sevoflurane on Pulse Rate in Patients Under Going General Surgery - Ismael Waadullah Ismael; Husam K. Mghames; Mortatha A. Khulaif; Zahraa T. Jaafer (Journal of Techniques)
The inhalational agents are very important to maintain the depth of anesthesia, provide analgesia and muscle relaxant. Many factors have effect of anesthetic gases, including type in an anesthetic agents and its MAC and other properties and postoperative stays. This study were designed to comparison between isoflurane  and sevoflurane as inhalational agents on the pulse rate during general anesthesia.